2006
DOI: 10.1038/sj.ejcn.1602473
|View full text |Cite
|
Sign up to set email alerts
|

Serum prostate-specific antigen but not testosterone levels decrease in a randomized soy intervention among men

Abstract: Background: Low prostate cancer incidence and high soy intake in Asian countries suggest a possible protective effect of soy foods against prostate cancer. The goal of this pilot study was to evaluate the feasibility of a randomized, crossover soy trial among men and to investigate the effects of daily soy intake on serum prostate-specific antigen (PSA) and testosterone levels. Methods: We randomized 24 men to a high or a low soy diet for 3 months. After a 1-month washout period, the men crossed over to the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…In another randomized, double-blind trial involving prostate cancer patients with rising PSA levels after radical prostatectomy or radiotherapy, administration of dietary supplements, which included soy and isoflavones, resulted in delayed PSA progression (81). A randomized trial with data from 23 men (aged 58.7±7.2 years) found a 14% decline in serum PSA levels when the subjects were on high soy diet (two servings of soy per day) (82). Another phase II trial with isoflavones reported a significantly lowered PSA slope in the intervention group supporting an effect of isoflavones on PSA (83).…”
Section: Preclinical and Clinical Studiesmentioning
confidence: 99%
“…In another randomized, double-blind trial involving prostate cancer patients with rising PSA levels after radical prostatectomy or radiotherapy, administration of dietary supplements, which included soy and isoflavones, resulted in delayed PSA progression (81). A randomized trial with data from 23 men (aged 58.7±7.2 years) found a 14% decline in serum PSA levels when the subjects were on high soy diet (two servings of soy per day) (82). Another phase II trial with isoflavones reported a significantly lowered PSA slope in the intervention group supporting an effect of isoflavones on PSA (83).…”
Section: Preclinical and Clinical Studiesmentioning
confidence: 99%
“…However, a few studies conducted in subjects with high baseline PSA revealed a decrease in the PSA level while on soy supplementation [63]. Data from a randomized crossover study performed by Maskarinec et al [59] in 23 healthy men with a mean age of 58 years revealed a 14% statistically significant decline in PSA with no change in testosterone level when the subjects were given a high soy diet compared with a low soy diet. A randomized controlled trial done by Ide et al [60] in Japenese men (n=85) with a median age of 73 years showed that PSA levels significantly decreased in the supplement treated group (isoflavones 40 mg plus curcumin 100 mg daily for 6 months) only in those subjects with a baseline PSA level greater than 10 ng/ml, with no prostate cancer.…”
Section: Human Trials Of Phytoestrogens and Prostate Health And Diseasementioning
confidence: 99%
“…One randomized, placebocontrolled trial of 12 weeks treatment with genistein in men with early prostate cancer found no significant difference in PSA levels between the treatment and placebo groups (Kumar et al, 2004), although the authors suggested that surrogate measures were being affected by treatment. Other trials support the idea that isoflavones, even given over relatively short periods of time, can possibly slow the rate of rise of PSA, though no statistically significant conclusions can be drawn (Dalais et al, 2004;Hussain et al, 2003;Maskarinec et al, 2006;Pendleton et al, 2008 (Davis et al, 2000;Takahashi et al, 2006;Tepper et al, 2007) b. c. d. (Nakamura et al, 2002;Tsui et al, 2008 (Davis et al, 1998) b. (Palozza et al, 2010) c. (Benitez et al, 2007;Kuwajerwala et al, 2002) d. (Davis et al, 1998;Lian et al, 1998) c. (Benitez et al, 2007;Kuwajerwala et al, 2002;Mitchell et al, 1999) d. (Bhatia & Agarwal, 2001;Kazi et al, 2003;Rice et al, 2007) c. (Benitez et al, 2007;Kuwajerwala et al, 2002) d. Protein tyrosine kinase a. Inhibition of EGF tyrosine kinase activation by genistein c. Resveratrol inhibits tyrosine kinase d. Curcumin inhibits EGF-R signaling a.…”
Section: Clinical Studies In Prostate Cancermentioning
confidence: 99%
“…As the studies in Table 3 Non -significant decline in testosterone levels, but compensated rise in LH levels (Rannikko et al, 2006) High or low soy diet for 3 months N=24, randomized crossover to alternative diet after 1 month washout Decline of PSA (not significant) of 14% while on high soy diet (Maskarinec et al, 2006) Lycopene with or without soy isoflavones for 6 months N=71, includes hormone sensitive and resistant patients. Randomized trial.…”
Section: Clinical Studies In Prostate Cancermentioning
confidence: 99%